DISTRIBUSI DAN STABILITAS PENDAPATAN RUMAH TANGGA PEDESAAN MENURUT PERBEDAAN AGROEKOSISTEM - Supadi, .; Nurmanaf, A. Rozany (Lampung University)
The objective of this research is to identify and analyze the distribution and stability of family income in connection to agroecosystem.Â This research was carried out in three provinces; these are Central Java, Lampung and South Sulawesi. In every province the study selected 4 villages that is classified based agroecosystems, i.e. wet land and dry land villages. The study interviewed 50-60 households who were the Patanas research household sample. The study employs descriptive analysis. Result of the research showed that income from agricultural sector has a dominant contribution, generally. Nevertheless, this domination tends to shifts gradually where the proportion of non-agricultural income increases significantly. Household income distribution in the village falls into high skewed criteria, especially in wet land villages. Household income in wet land villages fluctuates more than those of in dry land villages. Contribution of agricultural income is dominant in wet land villages, but it is a seasonal income. Farmers in dry land has more non-agricultural activity than those of in wet land villages.